USM SETS REALISTIC AIMS FOR 2020 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PULAU LANGKAWI, October 2015 – Universiti Sains Malaysia (USM) is setting realistic aims to be achieved by the year 2020 with its highlyfocused strategic planning that would entail the involvement of the whole USM community.